2022
DOI: 10.1111/ppl.13659
|View full text |Cite
|
Sign up to set email alerts
|

The miR159‐MYB33‐ABI5 module regulates seed germination in Arabidopsis

Abstract: Drought stress restricts crop productivity and exacerbates food shortages. The plant hormone, abscisic acid (ABA), has been shown to be a pivotal player in the regulation of drought tolerance and seed germination in plants. ABA accumulates under abiotic stresses to promote miR159 expression. miR159 is an ancient and conserved plant miRNA that plays diverse roles in plant development, seed germination, and drought response in Arabidopsis. Our previous studies demonstrated that miR159 regulates the vegetative ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The upstream region of MIR159 was analyzed, revealing the presence of ABRE response elements. Previous studies have shown that the application of exogenous ABA can induce the expression of miR159 and inhibit the expression of MYB33 , reducing the sensitivity of plants to ABA, which plays a vital regulatory role in the transformation process of seed germination and breaking dormancy (Achard et al., 2004; Guo et al., 2017; Jiang et al., 2022; Reyes & Chua, 2007). Overexpression of MYB33 and MYB101 has been observed to result in hypersensitivity to ABA in Arabidopsis and tomato (Hou et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The upstream region of MIR159 was analyzed, revealing the presence of ABRE response elements. Previous studies have shown that the application of exogenous ABA can induce the expression of miR159 and inhibit the expression of MYB33 , reducing the sensitivity of plants to ABA, which plays a vital regulatory role in the transformation process of seed germination and breaking dormancy (Achard et al., 2004; Guo et al., 2017; Jiang et al., 2022; Reyes & Chua, 2007). Overexpression of MYB33 and MYB101 has been observed to result in hypersensitivity to ABA in Arabidopsis and tomato (Hou et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…ABI5 acts as a central transcription factor and marker that negatively regulates drought stress in Arabidopsis and rice (Zou et al, 2008; Collin et al, 2020; Ju et al, 2020; Li et al, 2021; Wang et al, 2021; Jiang et al, 2022). In Brachypodium distachyon , HD1‐ OE plants showed improved tolerance to drought stress by reducing the expression of ABI5 (Song et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TaNCED1 from wheat ( Triticum aestivum L.) resulted in higher drought tolerance in tobacco ( Nicotiana tabacum L.) (Zhang et al, 2014). ABA‐INSENSITIVE 5 ( ABI5 ) is a central ABA‐responsive gene that negatively regulates drought stress in plants (Zou et al, 2008; Collin et al, 2020; Ju et al, 2020; Li et al, 2021; Wang et al, 2021; Jiang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The role of MYB 33/101 TFs in ABA signaling has already been proven for seed germination in the case of Arabidopsis (Reyes & Chua, 2007 ). Recently in Arabidopsis , the role of mir159‐MYB33‐ABI5 in seed germination and drought response has been described (Guo et al, 2021 ; Jiang et al, 2022 ). However, the role of these TFs and MYB65 in the drought response has never been tested.…”
Section: Discussionmentioning
confidence: 99%